Patronage as politics in South Asia - Piliavsky, Anastasia, 1981- (New York : Cambridge University Press, 2014)
"Focuses on the persistent norms of conduct and communication, forms of economic and ritual exchange, and mutual expectations, which distinguish patronage patterns in South Asian countries from those observed anywhere else"--
Includes bibliographical references and index.
BIGD
Keywords: Patronage, Political -- South Asia; Social structure -- South Asia; Political sociology